The Effect of Smartphones Media to Improve Critical Thinking Skills Student of Elementary School - Imas Srinana Wardani; Ari Widodo; Munir (Jurnal Penelitian Pendidikan IPA, 2024)
21st-century learning is oriented towards digital lifestyles. Smartphones are a digital technology that many students already have. Smartphones can be used in learning activities. Smartphones have features that can be used for learning activities. Smartphones can make students more actively engaged in the learning process. This study aims to improve the critical thinking skills of elementary school students through the use of smartphones. This research is a quantitative study using Quasi-experimental method. The research design used is the non-equivalent control group design where the sample consists of 43 students. Research data were collected using a multiple-choice test of critical thinking with 21 questions on the human respiratory system material with 5 aspects of thinking questions. The results showed a significant difference between the experiment and control group. This means that learning using smartphones can improve critical thinking skills. It can be concluded that learning becomes more enjoyable with the use of smartphones because students are given time to ask questions, argue about the results of experiments recorded using smartphones, so that students can improve their critical thinking skills.